Reframing Purgatory: An Issuantist Proposal Grounded in Aeveternity - Viezzi, Devid (New blackfriars, 2026)
In this paper, I present an analysis of purgatory from an issuantist perspective – an approach that seeks to reconcile the concept of a loving God with the doctrine of eternal hell. Issuantism posits that both heaven and hell originate from God’s love, and I extend this framework to purgatory, offering a new interpretation of its eschatological significance. After examining the views of influential figures such as Joseph Ratzinger and Jerry Walls, I argue that purgatory must be understood as a condition outside of time to maintain theological consistency. I propose a model of purgatory located within an aeveternal dimension – an intermediate state between time and eternity – as a way to resolve tensions concerning temporality, moral agency, and the soul’s orientation toward heaven.